هيئة اليدين في الصلاة من الركوع حتى السلام : دراسة فقهية مقارنة - الفراجى، محمد سلمان محمود حديد; حسين، صفاء علي (جامعة الأنبار - كلية العلوم الإسلامية, 2010)
فالحمد لله الذي جعلنا من أمة النبي محمد (صلى الله عليه وسلم) هذه الأمة المرحومة والشاهدة على من سبقها من الأمم والتي خصها بشريعة جمعت كل الشرائع السابقة لتكون صالحة لكل زمان ومكان ولأن الصلاة عماد الدين ومن أجل معرفة الهيئة الصحيحة الواردة عنه (صلى الله عليه وسلم) لليدين ليبتعد المسلم الذي ينشد الحق عن الهيئات التي لم ترو عنه (صلى الله عليه وسلم) ويأخذ بما جاء به المصطفى (صلى الله عليه وسلم) اخترت هذا الموضوع (هيئة اليدين في الصلاة) ليكون مدار بحثي هذا العام ولكثرة المسائل قسمته إلى جزيئن الأول: هيئة اليدين من تكبيرة الإحرام حتى الركوع وقد تم نشره والحمد لله تعالى والثاني هيئة اليدين من الركوع حتى السلام وهو الذي بين يديك إذ درست المسائل دراسة فقهية مقارنة مع المذاهب الإسلامية وهي بعد المذاهب الأربعة مذهب الإمامية ومذهب الزيدية ومذهب الظاهرية ثم قمت بتخريج الأحاديث والترجيح ونتج عن البحث عدة نتائج أهمها ما يأتي: \ 1.\ أن السنة للمصلي أن يأخذ الركب باليدين في الركوع. \ 2.\ أن المصلي يرفع يديه إذا رفع رأسه من الركوع. \ 3.\ أن الراجح عدم وضع اليمين على الشمال في الاعتدال من الركوع. \ 4.\ كراهية أن يفترش المصلي ذراعيه. \ 5.\ أن أول ما يقع من المصلي على الارض ركبتاه وإذا نهض رفع يديه قبل ركبتيه. \ 6.\ أن المصلي يرفع يديه في القنوت وتكبيرات العيدين وتكبيرات الجنازة. However, After thanking Allah who make us the nation of the prophet muhammed peace and blessing be upon him, this mercified nation that will be a witness on the previous nations. It is specialized by sharia (law) that summed up all the laws of the previous nations. to be valid for every time nad place. For the prayer ia Imad Al-Din, it is important to know or find the right form of hands that comes from the prophet peace be upon him; so that the researcher chooses this topic (the form of hands in prayer) to be the substance of the research for this year. Because of the number of questioners, the researcher divided his topic into two parts:- The first includes (the form of hands from the opening campuses until kneeling ) and it is published. While the second includes (the form of hands from kneeling until the peace at the end of prayer. \ If the questioner is examined by, doctrinal (philological) study compared to the Islamic doctrines. This doctrinal study is after the four doctrines and includes Al-Imamiya doctrine, Al-Zaidiya doctrine and Al-Thahiriya doctrine. Then, the researcher examines the traditions and gives the mast correct opinion. As a result, several conclusion are reached at: They are as follow: \ 1.\ The suna recommonds the worshiper to take the knees by hands. \ 2.\ A worshiper should raise his hands when he raises his head from kneeling. \ 3.\ It is the most correct that not to put the right hand one the left one after moderating from the kneeling. \ 4.\ It is of hateness that A worshiper spread or sit his arms. \ 5.\ The first thing the worshiper should put on the ground in prayer is the knees. And when he gets up he should raise his hand before knees. \ 6.\ A worshiper should raise his hands in qunoot and the Eid Takbeerat and funeral.
Keywords: المذاهب الاسلامية -- الصلاة ( فقه اسلامي) -- الفقه الاسلامي -- تكبيرة الاحرام -- صلاة الجماعة -- صلاة الجنازة